2017
DOI: 10.3390/su9010072
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining Regional Advantages in Manufacturing: Skill Accumulation of Rural–Urban Migrant Workers in the Coastal Area of China

Abstract: Extant research pays little attention to unorganized migrant workers' skill accumulation/upgrading from the perspective of the labor supply. This paper takes China as an example to explore the factors influencing the skill accumulation of rural-urban migrant workers (RUMWs), with the purpose of discovering how to sustain or reshape regional competitive advantages by improving RUMWs' skill accumulation. Structured questionnaire surveys were adopted for data collection in Suzhou City, Jiangsu Province and Taizho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 69 publications
(87 reference statements)
0
6
0
Order By: Relevance
“…However, several studies have reported negative innovation effects on company financial performances. For example, innovation negatively affected the financial performances of architectural companies in Nigeria due to the speculative nature of the industry (Oluwatayo et al , 2016) and contrary to other studies, Zhu et al (2017) found that only marketing innovations improved small and medium enterprises (SME) economic performances in Zhejiang Province, China. These contradictions suggested that other variables were mediating and/or moderating the positive relationship between innovation and financial performance.…”
Section: Introductionmentioning
confidence: 60%
“…However, several studies have reported negative innovation effects on company financial performances. For example, innovation negatively affected the financial performances of architectural companies in Nigeria due to the speculative nature of the industry (Oluwatayo et al , 2016) and contrary to other studies, Zhu et al (2017) found that only marketing innovations improved small and medium enterprises (SME) economic performances in Zhejiang Province, China. These contradictions suggested that other variables were mediating and/or moderating the positive relationship between innovation and financial performance.…”
Section: Introductionmentioning
confidence: 60%
“…The contrasting results stem from the differences in institutions, organisation of employers and labour, and training systems (Toner, 2008). Globalisation speeds up the development of HCES, which is a synthesised space of a firm's internal labour-management relations and inter-organisational relations (Zhu et al, 2017), to foster the exchange of local and external knowledge.…”
Section: Spaces Of Human Capital Accumulationmentioning
confidence: 99%
“…In the research on industrial cooperation network, some researchers believe that the strategies of cooperation or competition among enterprises in cluster network directly affect the innovation performance (Felzensztein et al, 2018). The collective learning of enterprises in the cluster network can reshape their innovation ability and help to improve the overall innovation performance (Zhu et al, 2017). Taking the industrial cluster network in Canada as an example, Bramwell et al (2008) analyzed the transfer process of innovation knowledge in the global and local network structures and concluded that local and global innovation knowledge, learning process and government policies are helpful to improve the performance of industrial cluster network.…”
Section: Related Workmentioning
confidence: 99%